Increasing the operating lifetime of green phosphorescent organic light emitting diodes by reducing charge accumulation at the interface. Issue 6 (27th January 2023) - Wu, Yibing; Luo, Jianhui; Lin, Chengwei; Zhu, Tengfei; Qiao, Xianfeng; Yang, Dezhi; Dai, Yanfeng; Sun, Qian; Chen, Jiangshan; Ma, Dongge
Abstract : Increasing the operating lifetime of green phosphorescent OLEDs by inserting a thin layer of TCTA to reduce charge accumulation at the interface is reported. Abstract : The stability and degradation mechanism of phosphorescent organic light emitting diodes (OLEDs) has been an unresolved problem in the past decades. Here, we found that electron accumulation at the interface between the electron blocking layer and the emitting layer is one of the reasons for device degradation. By inserting a thin layer with a shallower LUMO level than that of the electron transporting layer between the emitting layer and the electron transporting layer, we successfully reduced the density of electrons at the interface and greatly improved the lifetime of the resulting green phosphorescent OLEDs. The half decay lifetime LT50 at the initial luminance of 1000 cd m −2 reached as high as 399 h, which is 1.7 times longer than that of the compared device without a thin layer.